Diagnostics in Children and Adolescents with Suspected or Confirmed Pulmonary Hypertension. (June 2017) - Koestenberger, Martin; Hansmann, Georg; Apitz, Christian; Latus, Heiner; Lammers, Astrid
Summary: We provide a practical approach on the initial assessment and diagnostic work-up of children and adolescents with pulmonary hypertension (PH). Transthoracic echocardiography (TTE) often serves as initial study tool before invasive cardiac catheterization. Misinterpretation of TTE variables may lead to missed or delayed diagnosis with devastating consequences, or unnecessary invasive diagnostics that have inherited risks. In addition to clinical and biochemical markers, serial examination of patients with PH using a standardized TTE approach, determining conventional and novel echocardiographic variables, may allow early diagnosis and treatment in paediatric PH. Cardiac magnetic resonance imaging and computed tomography represent important non-invasive imaging modalities, that together with TTE may enable comprehensive assessment of ventricular function and pulmonary hemodynamics. Invasive assessment of haemodynamics (ventricular, pulmonary) and testing of acute vasoreactivity in the catheterization laboratory is still the gold standard for the diagnosis of PH and pulmonary hypertensive vascular disease (PHVD) in children and for the initiation of specific PH therapy. We suggest the regular assessment of prognostic TTE variables as part of a standardized approach for initial diagnosis of children with PH. Overreliance on any single TTE variable should be avoided as it detracts from the overall diagnostic potential of a standardized TTE examination for PH.